Formulasi Pasta Buah Merah (Pandanus conoideus Lamk) dan Tepung Ubi Jalar Mikmak (Ipomea batatas L) Lokal Wamena Untuk Produksi Saus Buah Merah Pedas - Setiarto, Raden Haryo Bimo; Widhyastuti, Nunuk; Agustin, Nety; Rahmawati, Rahmawati; Wawo, Albert Husein (Faculty of Animal and Agricultural Sciences, Diponegoro University)
Red fruit (Pandanus conoideus Lamk) and sweet potatoes (Ipomea batatas L) is the endemic plant that grows in the plains of Wamena, Papua. Availability is quite abundant and it has not been utilized to the maximum, so that required further processing to increase its economic value. This study aims to determine the best formulation between red fruit paste and sweet potato flour to obtain spicy red fruit sauce product with good nutritional quality and organoleptic properties. The formulation of red fruit paste and sweet potato flour was done with six levels ie A1 (100%: 0%), A2 (95%: 5%), A3 (85%: 15%), A5 (80%: 20%), and A6 (75%: 25%). The quality of red spicy fruit sauce tested is physical quality (viscosity), chemical quality (total dissolved solids and pH value), and organoleptic quality (hedonic test and hedonic quality with color, taste, aroma and consistency parameters). Based on the results of the research, the best formulation was found in A2 treatment with the ratio of red fruit paste and sweet potato flour (95%: 5%). The product of spicy red fruit sauce produced is in conformity with Standard National Indonesian (SNI) as reference SNI 01-2976-2006 about chili sauce quality requirement on total parameters of soluble solids, total bacteria, total mold, flavor, and taste.